O046 Incidental appendicectomy in pancreas transplantation: a single-centre study. (22nd July 2022) - Hussein, A; Gill-Barman, B; Karydis, N; Callaghan, C
Abstract: Introduction: Pancreas transplantation is associated with a significant rate of surgical complications, some of which have similar clinical features to acute appendicitis. An incidental appendicectomy (IA) at the time of pancreas transplantation could reduce future diagnostic uncertainty. This study aimed to establish the number of IA undertaken during pancreas transplantation in our unit and examine outcomes. Of those patients that did not undergo an IA, we identified those that subsequently required intervention for their appendix. Methods: A database of patients who underwent a pancreas transplant in our unit from 01/01/2012 to 10/12/2020 was obtained and patients were followed up until 01/03/2021. Electronic records were examined. Standard statistical analyses were undertaken and death-censored graft survivals were compared using the log-rank test. Results: 243 patients underwent a pancreas transplant. Of the 227 (93%) patients that had not previously had an appendicectomy, 53 (23%) underwent an IA during transplantation. There were no complications and 2 carcinoid tumours were identified. Of the 174 (77%) patients that did not undergo an IA, 3 (2%) patients required subsequent intervention for the appendix. There was no statistically significant difference in operative time (p=0.06), index inpatient length of stay (p=0.50), ICU stay (p=0.80), pancreatic graft survival (p=0.50), or kidney graft survival (p=0.70) between patients who had an IA and those who did not. Conclusion: IA during pancreas transplantation appears to be safe, and does not significantly prolong pancreas transplantation or adversely affect other outcomes. Surgeons should consider whether incidental appendicectomy should become standard practice. Take-home message: Appendiceal complications after pancreas transplantation can be challenging and surgeons should consider whether incidental appendicectomy should become standard practice.